Transcriptomic Analysis of the Interaction Between FLOWERING LOCUS T Induction and Photoperiodic Signaling in Response to Spaceflight - Wang, Lihua; Xie, Junyan; Mou, Chenghong; Jiao, Yuwei; Dou, Yanhui; Zheng, Huiqiong (Frontiers in Cell and Developmental Biology, 2022)
Spaceflight has an impact on growth and development of higher plants at both vegetative stage and reproductive stage. A great deal of information has been available on the vegetative stage in space, but relatively little is known about the influence of spaceflight on plants at the reproductive stage. In this study, we constructed a transgenic Arabidopsis thaliana plants expressing flowering control gene, FLOWERING LOCUS T (FT), together with green fluorescent protein gene(GFP) under control of a heat shock-inducible promoter (HSP17.4), by which we induced FT expression inflight through remote controlling heating shock treatment. Inflight photography data showed that induction of FT expression in plants in space could counteract the impact of spaceflight and promote flowering. Whole-genome microarray analysis of gene expression changes in leaves of wild-type and these transgenic plants grown under the long-day and short-day photoperiod conditions in space indicated that the function of the photoperiod-related spaceflight response genes are mainly involved in protein synthesis and post-translation protein modulation, notably protein phosphorylation. In addition, changes of circadian component gene expression in response to spaceflight under different photoperiod indicated that roles of circadian oscillator could act as integrators of spaceflight response and photoperiodic signals in Arabidopsis plants grown in space.